A função do Jornal O Lavrador como meio difusor da formação do professor ruralalista de Juazeiro do Norte. - Silva, Mirelle Araújo da (2009)
The present work deals with the teacher’s formation in the rural area of the State of Ceará, focusing on the teacher’s ideal of the Normal School of Juazeiro do Norte having as topic of research the newspaper O Lavrador during 1934 through 1974, a period that corresponds to the early years of functioning of that School until its closing. This research found that the foundation of that educational institution had as its main goal to make available to the students a rural education because this objective is directly realated to the historical valorization of the agriculture by the northeastern rural agrarian elite, as a vital way to achieve the progress after 1930 Revolution. The aims of this research were: 1) Set up the commented chronology of the school in order to allow a reflexive appreciation of its trajectory. 2) Understand the pedagogical bases of the school, focusing on the rural thought and the support of the New School directrixes. 3) Try to identify and to analyse the changings and the continuities in the formation proposals of the teachers through the 113 issues published during the period of time mentioned above(1934-1974). We used historic and printed sources, these undestood in their multiple possibilities of materialization, cross reference and interpretation, using as an universe of search 113 editions of the O Lavrador, once this newspaper was published for this very school, and distributed by it in the first year of his foundation. We tried to show the results obtained in the contents examining, emphasizing the attention given by that paper on subjects related to the agricultural worker’s life, main events and pedagogical pactices of the school and the divers articles written by the very students. The five decades studied in which the paper existed, allowed us to delimitate de differences and we were able to identify the following features: 1) 1930 – it was the beginning and also the golden era of the school showing the prestige and the notoriety of the Pedagogical Ruralism had in the education of Ceará State; 1940 – the continuity of the previous decade with intense activities; 3) 1950 – is remembered as the time of the publication of many speeches on Ruralims and the celebration of the birthday of Mrs. Amélia; 4) 1960 – it is the beginning of the decline of the issuing of the newspaper and 5) 1970 – it is the end of the school due to the lack of the rural spirit that animate the school during its entire life. The trajectory of the paper was one of deep finnancial difficulties. The word “fight” is always linked to the celebration of the anniversary of the paper as a demonstration of the finnancial difficulties faced by that institution.